The receptor-like cytoplasmic kinase BSR1 mediates chitin-induced defense signaling in rice cells. Issue 8 (3rd August 2017) - Kanda, Yasukazu; Yokotani, Naoki; Maeda, Satoru; Nishizawa, Yoko; Kamakura, Takashi; Mori, Masaki
Abstract: Broad - Spectrum Resistance 1 ( BSR1 ) encodes a rice receptor-like cytoplasmic kinase, and enhances disease resistance when overexpressed. Rice plants overexpressing BSR1 are highly resistant to diverse pathogens, including rice blast fungus. However, the mechanism responsible for this resistance has not been fully characterized. To analyze the BSR1 function, BSR1 -knockout ( BSR1 -KO) plants were generated using a clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) system. Experiments using suspension-cultured cells revealed that defense responses including H2 O2 production (i.e. oxidative burst) and expression of defense-related genes induced by autoclaved conidia of the rice blast fungus significantly decreased in BSR1 -KO cells. Furthermore, a treatment with chitin oligomers which function as microbe-associated molecular patterns (MAMPs) of the rice blast fungus resulted in considerably suppressed defense responses in BSR1 -KO cells. These results suggest that BSR1 is important for the rice innate immunity triggered by the perception of chitin. Abstract: : The rice defense responses triggered by chitin perception are mediated by the receptor-like cytoplasmic kinase BSR1.